2014
DOI: 10.1108/jima-05-2012-0029
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Iranian female Muslim consumer impulse buying behaviour used as a form of retail therapy

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
(53 reference statements)
2
7
0
1
Order By: Relevance
“…The results showed that there is a positive correlation to online impulse buying. Similar results were obtained by previous researchers (Bandyopadhyay, 2016;Mohan, Sivakumaran, & Sharma, 2013;Nayebzadeh & Jalaly, 2014), that impulse buying tendency positively affects impulse buying behavior. Chusniasari & Prijati (2015) found results that hedonic shopping has a significant and positive influence on impulse buying of Pointbreak Tunjungan Plaza Surabaya's customers.…”
Section: Hypothesis Testing Resultssupporting
confidence: 91%
“…The results showed that there is a positive correlation to online impulse buying. Similar results were obtained by previous researchers (Bandyopadhyay, 2016;Mohan, Sivakumaran, & Sharma, 2013;Nayebzadeh & Jalaly, 2014), that impulse buying tendency positively affects impulse buying behavior. Chusniasari & Prijati (2015) found results that hedonic shopping has a significant and positive influence on impulse buying of Pointbreak Tunjungan Plaza Surabaya's customers.…”
Section: Hypothesis Testing Resultssupporting
confidence: 91%
“…Findings from latest research also indicate the role of SE in impulse buying. Nayebzadeh and Jalaly (2014) posited that SE has a significant role in impulse buying and a negative relationship between SE and impulse buying is possible. A study by Amir et al (2014) revealed that SE and impulsivity are related to impulsive buying behavior.…”
mentioning
confidence: 99%
“…Customers with the deep involvement of religiousness have interdependence and avoid experiencing new technology and products. Furthermore, results show that religious consumers are more satisfied with normal matters of life (Nayebzadeh & Jalaly, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…The existing literature established that religiosity influences consumer evaluations about products and services (Mokhlis, 2009), pricing practices (Arli & Tjiptono, 2018;Battour, Ismail, Battor, & Awais, 2017) and promotions practices (Mansour & Diab, 2016) of marketers. Furthermore, significant relationship was found between religiosity and behavioral outcomes like status-seeking (Yeniaras & Akkemik, 2017), materialism (Agarwala et al, 2019) brand switching (Choi, 2010), risk aversion (Adhikari & Agrawal, 2016), impulsiveness (Musadik & Azmi, 2019), emotions and satisfaction (Nayebzadeh & Jalaly, 2014).…”
Section: Introductionmentioning
confidence: 99%